Differences in treatment response and survival between HER2(2+)/FISH-positive and HER2(3+) breast cancer patients after dual-target neoadjuvant therapy: a matched case-control study - Zhou, Sicheng; Qin, Xuhui; Xing, Wei; Xu, Zhao; Wei, Chunlv; Ren, Yining; Gong, Zixing (Frontiers in Oncology, 2025)
BackgroundThe efficacy of neoadjuvant therapy (NAT) comprising dual-target drugs has been confirmed among patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer (BC). Therefore, we explored the differences in responses to NAT and prognosis between patients with HER2(3+) and HER2(2+)/fluorescence in-situ hybridization (FISH)-positive BC after TCbHP-based dual-target NAT.MethodsData from patients with HER2-positive invasive BC who underwent NAT and radical surgery between January 2019 and December 2022 at the Peking University First Hospital and Cancer Hospital of Chinese Academy of Medical Sciences were retrospectively summarized. Propensity score matching (PSM) was used to reduce confounding effects. Pathological complete response (pCR) and invasive disease-free survival (IDFS) were evaluated to respectively reflect therapeutic response and patients’ survival status.ResultsWe selected 132 BC patients (66 pairs) through PSM form a cohort of 308 patients. The pCR rate of patients in the HER2(3+) group was significantly higher than that in the HER2(2+)/FISH-positive group after NAT (P<0.001). Univariate and multivariate logistic regression analyses determined that pCR was significantly affected by tumor grade, hormone receptor (HR) status, HER2 status (P<0.05). The 3-year IDFS rate of HER2(3+) BC patients was better than that of HER2(2+)/FISH-positive BC patient (P=0.083), although the difference was not statistically significant. Furthermore, multivariable Cox regression analysis exhibited that positive lymph node, HER2(3+), and pCR were independent prognostic factors for IDFS.ConclusionHER2(2+)/FISH-positive BC patients exhibited worse treatment response and prognosis than HER2(3+) BC patients after dual-target NAT, indicating that HER2 expression level is a crucial factor influencing the therapeutic efficacy and prognosis of BC patients after TCbHP-based dual-target NAT.